Strategic Performance Measurement System in Higher Education in Indonesia: New Public Management Approach - Parama Santati; Sulastri Sulastri; Badia Perizade; Marlina Widiyanti (Faculty of Economics, Universitas Sriwijaya, 2022)
This research is a descriptive overview to describe the alignment between the criteria and measurements of several performance indicators compiled in the university's strategic plan. Key Performance Indicators (KPI) as indicators of organizational performance based on the Vision, Mission, and Organizational Strategy which are derived from Key Performance Indicators and Program Performance Indicators or Activity Performance Indicators. The alignment measurement method uses the correspondence analysis technique. This study finds that most of the measurement criteria are still dominated by the input aspect, with economic criteria. Performance measurement that focuses on input criteria will have an impact on 1 the orientation of higher education on the budget and does not describe how well the objectives of the program are being implemented. Higher education KPIs should be more result-oriented, the impact of which is on public trust, brand image, reputation, and university performance